The relationship between self-regulation, self-efficacy, and psychological well-being among the Salahaddin university undergraduate students in Kurdistan - Salleh, Reben Ramadhan (UMY Publication, 2021)
Self-regulation, self-efficacy, and psychological well-being are essential requirements in the academic environment. Psychological well-being is indispensable for students’ emotional balance and healthy growth and development. The recent study investigated the relationship between self-regulation, self-efficacy, and psychological well-being among Kurdish students at Salahaddin University. The objectives of the research are as follows: (1) to examine the prevalence level of selfregulation, self-efficacy, and psychological well-being among the Salahaddin University undergraduate students; (2) to examine the relationship of self-regulation and self-efficacy with psychological well-being among the Salahaddin University undergraduate students; and (3) to examine the effect of self-regulation and self-efficacy on psychological well-being among the Salahaddin University undergraduate students. The study employed quota sampling, and there were 407 respondents selected for it. Analysis techniques were presented in descriptive, Pearson Correlation, and Multiple Regression Analysis (MRA). The research shows a low level of self-regulation and self-efficacy among the Salahaddin University undergraduate students. However, psychological well-being is high. The study further demonstrates a positive and statistically significant relationship between self-regulation, self-efficacy, and psychological well-being among the Salahaddin University undergraduate students. Finally, the study showed that only self-regulation significantly affected psychological well-being among the Salahaddin University undergraduate students